Early outcomes of one-stage combined osteotomy in Legg-Calve´-Perthes disease - Bhuyan, Basant Kumar (Indian J Orthop, 2016)
BACKGROUND: Legg-Calve´-Perthes disease (LCPD) is an idiopathic avascular necrosis of the femoral head. There are multiple approaches to the treatment of LCPD ranging from conservative management to a wide variety of surgical methods. Conservative management necessitates extreme degrees of abduction in an orthosis for a longer period of time which further jeopardize capital femoral head vascularity. Surgical containment methods are used in cases where it is desirable. Initial surgical containment methods are varus or varus-derotational osteotomy of the proximal femur or an innominate osteotomy as described by Salter and other pelvic osteotomies. The purpose of this study was to describe the early results of containment methods by one-stage combined osteotomy (femoral varus osteotomy and Salter innominate osteotomy) in patients with severe LCPD. MATERIALS AND METHODS: 23 children were operated in the age group of 4–9 years for LCPD by one-stage combined osteotomy procedure between January 2005 and June 2012. There were 19 boys and 4 girls, left hip involved in 10 cases and right in 13 cases. Preoperatively, they were classified according to Catterall, Joseph's stage and lateral pillar (LP) classification. Postoperatively, clinical results were evaluated in accordance with Ratliff classification and radiological assessment was made by Mose's index, modified Stulberg classification and Epiphyseal extrusion index. RESULTS: Seventeen hips were Catterall group III, 6 in group IV and all had two or more “head-at-risk” signs. There were 2 patients with stage IIA, 15 were in stage IIB and 6 were in stage IIIA as classified by Joseph's stage of disease. According to LP classification, 11 patients were group B, 3 were group B/C and 9 were in group C. At an average followup of 5.4 years (range 2–9.5 years), the clinical results were good in 12, fair in 9 and poor in 2. According to Mose scale, 8 patients had good results, 13 fair results and 2 had poor results. Based on modified Stulberg classification, there were 10 patients in group A, 11 in group B and 2 in group C. The average preoperative extrusion index was 23.6% which improved postoperatively to 9.5% at latest followup. CONCLUSIONS: The surgical treatment of LCPD with the best expected outcome is still a challenge. Advanced containment methods by one-stage combined osteotomy can be considered as an alternative treatment where femoral head subluxation or deformity which makes containment difficult or impossible by more conventional methods.